Plastics, microplastics, and human contamination: A literature review - de Carvalho, Marina Rocha; Teixeira, Alef Fontinele; Dias , Luana do Nascimento; Silva, Danielle de Jesus; Nascimento, Suzany Pedrosa; Pereira, Gabriel Estevão Nunes; Leite, Graziela Santos; Silva, Jamile Gabriela Almeida; Mendes, Jackson Rodrigues; Azevedo, James Werllen de Jesus; Lopes, Marcelo Henrique Silva; de Castro, Antonio Carlos Leal (Seven Editora, 2024)
Plastics are synthetic materials produced through the polymerization of monomers derived from oil or gas. Plastic waste causes several problems, affecting the environment, marine life, biodiversity, and the functioning of ecosystems. Plastic fragments can be ingested by various species, occurring records in the digestive system of various organisms. Microplastics (PMs) include small plastic particles ranging from 1 μm to 5 mm in size and are currently identified as one of the emerging environmental contaminants of greatest concern in aquatic ecosystems, especially in the marine environment. Microplastics can be transported into the body by dermal contact, ingestion, inhalation, and transfer through the food chain. The bioaccumulation of PMs can cause internal and external lesions, ulcers, blockage of the digestive tract, among other lethal and sublethal effects. Microplastics that enter the human body can contain chemicals that cause cancer, DNA mutations, toxic effects on reproduction, hormonal disruption, and affect various organs. Recurrent sources of microplastic for the aquatic system are sewage, drainage systems, tire wear, and plastic waste that is poorly managed or discarded on beaches. Microplastic contamination generates a decrease in fish stocks, influencing populations living in the vicinity of contaminated environments, such as the population living near the ALUMAR Private Use Terminal, São Luís, Maranhão. Therefore, research with microplastics is of fundamental importance for improving the quality of life of the population and the environment and can be associated with several Sustainable Development Goals (SDGs). DOI:https://doi.org/10.56238/sevened2024.018-066